SWOT ANALYSIS OF THE DEVELOPMENT OF NETWORK INTERACTION BETWEEN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS OF THE REPUBLIC OF KAZAKHSTAN IN THE VIRTUAL SPACE - Kolumbayeva, Sholpan; NARBEKOVA, B.; TANATOVA, A. (Pedagogy and Psychology, 2024)
The article presents an analytical review of theoretical material on the study of the problem of network interaction in virtual space and the identification of the attitude of Kazakhstani students of pedagogical specialties of higher educational institutions to virtual communication and interaction in social networks. The trends of the influence of the Internet and digital resources on the development of networking and learning are studied. A SWOT analysis of the features of youth network interactions in the virtual space is presented, recommendations are given on managing existing risks in the development of online student interaction in the digital educational space. The authors have developed two models, one is related to the influence of network interaction on the formation of a network communicative culture of students, the second represents a network communicative culture of interaction between students and university teachers.